Contesting Climate Futures: mapping misinformation narratives and networks on Telegram - Tucci, Giulia; Carneiro, Bia; Bastos, Joao Guilherme (2025)
“Contesting Climate Futures: mapping misinformation narratives and networks on Telegram” is a collaborative research project developed during the Digital Methods Initiative (DMI) Summer School 2025, under the theme “Social Media at a Crossroads, and the Sensitivity of AI Platforms.” All project materials are available under the Files tab of this OSF repository. They include datasets, analytical outputs, and visual documentation.The Datasets folder contains the main annotated dataset used for textual and thematic analysis, nodes and edges files required to reconstruct network graphs, and ranking of domains extracted.